Acute Effects of Blood Flow Restriction Training on Movement Velocity and Neuromuscular Signal during the Back Squat Exercise - García-Sillero, Manuel; Maroto-Izquierdo, Sergio; Galván-García, María; Benítez-Porres, Javier; Vargas-Molina, Salvador; Jurado‑Castro, José Manuel (MDPI, 2023)
The aim of this study was to verify the effects of blood flow restriction on movement velocity and muscle activity during the back squat exercise. Methods: Twenty-four university students participated in this study. In two randomized sessions 72 h apart, participants performed a 4-set protocol consisting of 30-15-15-15 repetitions performed at 30% of their one-repetition maximum in the back squat exercise. In both sessions, neuromuscular function was monitored by surface electromyography (EMG) and movement velocity (mean propulsive velocity (MPV), peak concentric velocity (Vmax), and the effort index (EI)). Blood flow restriction (BFR) was applied during exercise in one of the experimental sessions with 80% of full arterial occlusion pressure over lower limbs. Results: The BFR condition showed higher (p < 0.05) EI, peak, and rooted mean square normalized EMG in Set 1 compared to Set 2. Similar MPV and Vmax were observed in each set for both the BFR and control conditions. No significant differences were observed between conditions in any set. Conclusions: BFR did not imply changes in neuromuscular performance during low-intensity resistance training, but it might induce greater intra-series velocity loss and less excitation of the muscles involved.
Keywords: Transmisión neuromuscular; Ejercicio físico - Aspectos fisiológicos; Neuromuscular performance; Blood flow restriction; Occlusion; Resistance training; Velocity; EMG